Improved response of the Ti30Ta experimental alloy after surface treatment for dental applications - Souza, Marisa Aparecida [UNESP]; Kimaid, Maria Isabel Eboli [UNESP]; Capellato, Patrícia [UNESP]; Konatu, R. T. [UNESP]; Rezende, Maria Cristina Rosifini Alves [UNESP]; Popat, K. C.; Claro, Ana Paula Rosifini Alves [UNESP] (Elsevier, 2013)
The purpose of the study was to evaluate the influence of the biomimetic surface treatment in osseointegration of experimental alloy Ti30Ta for dentistry applications. Methods and materials: Experimental alloy with Ta concentration of 30 wt% was produced from sheets of commercially pure titanium (99.9%) and tantalum (99.9%). Ingots were melted in an arc furnace under an argon atmosphere and re-melted ten times at least. They were homogenized under vacuum at 1100 °C for 86.4 ks to eliminate chemical segregation and cold-worked by swaging. Implants with 2.5 mm diameter and 2.0 mm of height were machined (Fig. 1a), treated and inserted in animals for in vivo study. The implants were submitted surface treatment according methodology development for our group. Analyzes were performed by Scanning Electron microscopy (SEM), Atomic Force Microscopy (AFM). Osteoblast morphology on Ti-30Ta alloys was examined after 4 and 7 days of incubation with MSCs using SEM imaging.
Keywords: Titanium; Dental alloy; Surface treatment